Creating pressure training environment for elite tennis players - Šimeček, Michal (2023)
Pressure training has emerged as a novel approach to prepare athletes for the demands of high-pressure situations, fostering their ability to adapt and perform optimally. This study aimed to investigate the utilization and effectiveness of pressure training among professional tennis players through interviews conducted with coaches at a professional tennis academy in southern Europe. By examining the methods employed by these coaches, this research sought to shed light on the multifaceted application of pressure training, encompassing mental, tactical, and physical dimensions of athlete readiness for competition. The study employed a qualitative research design, utilizing in-depth interviews to gather comprehensive insights from experienced coaches at the professional tennis academy in southern Europe. The interviews were conducted using a semi-structured format, allowing for a rich exploration of the coaches' perspectives, strategies, and experiences with pressure training. Findings from the study revealed that pressure training is an integral component of the coaching approach employed at the academy. Results showed five major themes – Perception of pressure, Stakes in Training, Benefits of Pressure, Negatives of Pressure and Coach and Player relationships. Coaches utilized a diverse range of strategies to expose players to pressure and create a controlled environment for them to develop essential mental skills. These strategies encompassed both simulated high-pressure scenarios and real-life competition experiences, effectively enabling players to enhance their decision-making abilities, emotional regulation, focus, and resilience. The outcomes of this study underscore the efficacy of pressure training as a means of enhancing performance and developing mental skills among competitive athletes. The findings demonstrate that pressure training, when implemented in a controlled environment and under the guidance of experienced coaches, can serve as a powerful tool for athletes to attain greater success in their respective sports. This research provides valuable insights into the practical implementation and benefits of pressure training at the academy. By leveraging pressure as a training stimulus, coaches effectively equip athletes with the mental fortitude, tactical acumen, and physical resilience required to thrive in high-pressure situations. The study's outcomes contribute to the growing body of knowledge surrounding sports psychology and training methodologies, offering a foundation for future research and practical applications in the field of athletic development.